The Effect of Individual Counseling on Students' Aggressive Behavior in Class IX C of SMP Negeri 3 Brebes in the 2022/2023 Academic Year - Muhammad Fikri Haikal; Sitti Hartinah; Hastin Budisiwi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to find out individual counseling and aggressive behavior in Class IX C students of SMP Negeri 3 Brebes for the 2022/2023 academic year. As well as to find out whether individual counseling has an effect on the aggressive behavior of Class IX C students of SMP Negeri 3 Brebes for the 2022/2023 academic year. This type of research is a survey method with a quantitative approach. In this study, the population used was Class IX C students at SMP Negeri 3 Brebes for the 2022/2023 academic year, totaling 29 students. Sampling in this study used a saturated sample, namely all members of the population were sampled, so that the sample in this study was 29 students with 16 male students and 13 female students. The results showed that the level of individual counseling services for students was in the high category. The level of aggressive behavior in students is in the high category. There is an influence of individual counseling services on aggressive behavior in students as evidenced by statistical testing of simple linear regression analysis, which shows that Ha is accepted. Suggestions in this study are that schools and teachers are expected to collaborate with parents of students to help schools evaluate the effectiveness of individual counseling services and ensure that students receive the necessary support at home